Late Effects After Haematopoietic Stem Cell Transplantation in ALL, Long-Term Follow-Up and Transition: A Step Into Adult Life - Diesch-Furlanetto, Tamara; Gabriel, Melissa; Zajac-Spychala, Olga; Cattoni, Alessandro; Hoeben, Bianca A. W.; Balduzzi, Adriana (Frontiers in Pediatrics, 2021)
Haematopoietic stem cell transplant (HSCT) can be a curative treatment for children and adolescents with very-high-risk acute lymphoblastic leukaemia (ALL). Improvements in supportive care and transplant techniques have led to increasing numbers of long-term survivors worldwide. However, conditioning regimens as well as transplant-related complications are associated with severe sequelae, impacting patients’ quality of life. It is widely recognized that paediatric HSCT survivors must have timely access to life-long care and surveillance in order to prevent, ameliorate and manage all possible adverse late effects of HSCT. This is fundamentally important because it can both prevent ill health and optimizes the quality and experience of survival following HSCT. Furthermore, it reduces the impact of preventable chronic illness on already under-resourced health services. In addition to late effects, survivors of paediatric ALL also have to deal with unique challenges associated with transition to adult services. In this review, we: 1) provide an overview of the potential late effects following HSCT for ALL in childhood and adolescence; 2) focus on the unique challenges of transition from paediatric care to adult services; and 3) provide a framework for long-term surveillance and medical care for survivors of paediatric ALL who have undergone HSCT.